ANALYSIS OF APOLIPOPROTEIN-B (APO-B) GENE IN ATHEROSCLEROSIS MICE GIVEN CURCUMINOID EXTRACT OF ZANTHORRIZA IN ORAL - Trini Susmiati; Rini Widayanti; Aris Purwantoro; Claude Mona Airin; Sarmin Sarmin (Jurnal Kedokteran Hewan, 2019)
The aim of this study was to investigate the apolipoprotein-B (apo-B) gene in atherosclerosis mice which were orally given curcuminoid extract of Curcuma xanthorriza. A total number of 30 white mice were split into 6 groups, the first group considered as control (without any treatment), second group as atherogenic feed control, the third group as extract control, while the fourth, fifth and sixth groups as atherogenic feed and curcuminoid Curcuma xanthorriza extract group treated with 5 mg/mouse, 10 mg/mouse and 15 mg/ mouse, respectively for three months. The blood samples were taken from all six groups for the deoxyribonucleic acid (DNA) analysis using total DNA isolation, DNA amplification with polymerase chain reaction (PCR), and DNA sequencing. The data analysis showed that 374 bp nucleotide sequence gen of apo-B from Rattus norvegicus in groups B, C, D, E, and F did not cause any changes in genes. The analysis showed the sequence of apo-B Rattus norvegicus gene in the treatment group was apparently identical with that of Rattus norvegicus group A as the control group without treatment. As conclusion, the administration of curcuminoid zanthorrizza to atherosclerosis mice did not change the gene structure of apo-B 100.